The Welfare of Farmed Ratites - Glatz, Phil; Lunam, Christine; Malecki, Irek (Animal Welfare ;, 2011)
This volume reviews, for the first time, the broad range of issues that affect the welfare of commercially farmed ratites.  Although ratites incorporate several families of flightless birds this book focuses on the most commonly farmed ratites, the ostrich, emu and rhea. The readers are taken on a journey through all sectors of the industry, which include breeding, incubation, hatching, brooding, rearing, growth, transport and processing, with an emphasis on husbandry and management protocols that can impact bird welfare and health. Also discussed is the structure and sensory innervation of the skin and digits of the birds, and the potential welfare implications of industry practices on these structures. Each chapter in this volume focuses on a particular aspect of the commercial farming of ratites with contributing authors from a broad range of disciplines.   .